Sosialisasi Pembuatan Ecoenzyme sebagai Solusi Alami untuk Kebersihan Lingkungan di Kelurahan Bontang Kuala - Munir, Rahmawati; Hamdani, Dadan; Hamdi, M. Khilal; Murtadha, Nayla Izzatil; Munir, Rahmiati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2025)
ABSTRACT: This community service activity aims to enhance environmental awareness and human resource capacity through the socialization of ecoenzyme as a natural solution for environmental cleanliness. The activity was conducted in Bontang Kuala Village, North Bontang District, with a focus on the production and utilization of ecoenzyme as an eco-friendly solution. The methods used consisted of three main stages: preparation of materials and tools for making ecoenzyme, presentation of the importance of environmental cleanliness, and hands-on practice of ecoenzyme production. The results of this activity showed an increase in community understanding of environmental cleanliness and the potential use of ecoenzyme in daily life. Participants were able to independently practice making ecoenzyme and are expected to apply it to maintain environmental cleanliness in Bontang Kuala Village.